Still catching attention: Sea Around Us reconstructed global catch data, their spatial expression and public accessibility. (August 2016) - Zeller, D.; Palomares, M.L.D.; Tavakolie, A.; Ang, M.; Belhabib, D.; Cheung, W.W.L.; Lam, V.W.Y.; Sy, E.; Tsui, G.; Zylich, K.; Pauly, D
Abstract: In 2005, the Sea Around Us described a website (www.seaaroundus.org ) which presented, for all maritime countries and large marine ecosystems in the world, one of the most basic information items required by policy makers and fisheries managers: what catch was taken within their jurisdictional boundaries, and which countries took it. Surprisingly, for many countries this kind of jurisdictionally and/or ecologically assigned data had not been readily available before then. Since the release of these spatialized data, this material has had major influence on how fisheries are perceived by policy makers in various countries and by the global scientific community, as well as by a growing list of other stakeholders such as non-governmental environmental organizations and the general public. Here, the Sea Around Us updates the fisheries science, policy, conservation and management audience on the extensively modified spatial allocation method and a substantially improved new website. Also, this contribution points to and describes the much improved catch data underlying this website. These data now account for catches for all countries in the world by fisheries sectors (industrial, artisanal, subsistence, recreational), after augmenting the officially reported landings data through the inclusion of comprehensively reconstructed data of previously unreported catches and major discards, for every maritime country or territory in the world, and their Exclusive Economic Zone (EEZ). Also presented are the extensively improved spatial allocation procedures which assign global catch data to the 180, 000 half degree spatial cells used by the Sea Around Us to subdivide the global ocean. The reconstructed data for 1950–2010 for all countries in the world and the High Seas, freely accessible and downloadable through the Sea Around Us web portal, will be updated regularly. It is hoped that these revised data and the substantially improved web utility will invigorate and assist the debate about the role of fisheries in a global framework as well as in national food security settings. Graphical abstract: Highlights: Officially reported fisheries catch data are incomplete. Missing marine catch data were estimated for all countries in the world, from 1950 to 2010. Global catch data were assigned to ecological and politically meaningful space. All data processes are described and all data are available in a new Sea Around Us website.